Effectiveness of Office Administration Governance in Improving the Quality of Administrative Services - Jamaluddin Jamaluddin; Sitti Anugrah Nur; Muh Darwis (Pinisi Journal of Education and Management, 2023)
The effectiveness of administrative governance in improving the quality of administrative services. This research aims to determine the effectiveness of office administration governance in improving the quality of administrative services at the Bone Village office, Bajeng District, Gowa Regency. This type of research is descriptive research using qualitative methods and approaches to determine the effectiveness of office administration governance in improving the quality of administrative services at the Bone Village office, Bajeng District, Gowa Regency. The number of informants in this study was 3 people, namely 1 head of the administration sub-division, and 1 financial staff employee. 1 from the administrative department. The data collection techniques used are the observation method, interview method, and documentation method. The data analysis techniques used by researchers are data reduction techniques, data presentation, conclusions, and verification. The results of this research show that the achievement of service targets can be realized well, leadership abilities and human resources are quality provide excellent service in providing services, and overcome problems experienced. This research can be used as a reference in improving the quality of administrative services by using the latest indicators to determine the effectiveness of office administration governance, which is different from previous research which still used previous indicators to measure the effectiveness of office governance in improving the quality of administrative services